Glutathione S-transferases in neonatal liver disease. Issue 8 (August 1992) - Mathew, J; Cattan, A R; Hall, A G; Hines, J E; Nelson, R; Eastham, E; Burt, A D
Abstract : AIMS: To investigate the distribution of alpha and pi class glutathione S-transferases (GST) in normal fetal, neonatal, and adult liver; and to examine changes in GST expression in neonatal liver disease. METHODS: alpha and pi class GST were immunolocalised in sections of formalin fixed liver tissue obtained from human fetuses (n = 21), neonates (n = 8), young children (n = 9) and adults (n = 10), and from neonates with extrahepatic biliary atresia (n = 15) and neonatal hepatitis (n = 12). Monospecific rabbit polyclonal antibodies were used with a peroxidase-antiperoxidase method. RESULTS: Expression of pi GST was localised predominantly within biliary epithelial cells of developing and mature bile ducts of all sizes from 16 weeks' gestation until term and in neonatal and adult liver. Coexpression of pi and alpha GST was seen in hepatocytes of developing fetal liver between 16 and 34 weeks' gestation. Although pi GST was seen in occasional hepatocytes up to six months of life, this isoenzyme was not expressed by hepatocytes in adult liver. By contrast, alpha GST continued to be expressed by hepatocytes in adult liver; this isoenzyme was also seen in some epithelial cells of large bile ducts in adult liver. No change was observed in the distribution of alpha GST in either neonatal hepatitis or extrahepatic biliary atresia. However, aberrant expression of pi GST was identified in hepatocytes of all but one case of extrahepatic biliary atresia but in only two cases of neonatal hepatitis. CONCLUSIONS: The phenotypic alterations noted in extrahepatic biliary atresia may result from the effect of cholate stasis. Evaluation of the pattern of pi and alpha GST distribution by immunohistochemical staining may provide valuable information in distinguishing between these two forms of neonatal liver disease.